2006
DOI: 10.1073/pnas.0601989103
|View full text |Cite|
|
Sign up to set email alerts
|

MTA1, a transcriptional activator of breast cancer amplified sequence 3

Abstract: Here we define a function of metastasis-associated protein 1 (MTA1), a presumed corepressor of estrogen receptor α (ERα), as a transcriptional activator of Breast Cancer Amplified Sequence 3 (BCAS3), a gene amplified and overexpressed in breast cancers. We identified BCAS3 as a MTA1 chromatin target in a functional genomic screen. MTA1 stimulation of BCAS3 transcription required ERα and involved a functional ERE half-site in BCAS3 . Furthermore, we discovered that MTA1 is acetylated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
113
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 25 publications
5
113
0
Order By: Relevance
“…In this context, the studies presented here provide a mechanistic basis for the contribution of MTA1 in positively modulating HMMR expression, leading to cell invasion. As MTA1 regulates its target genes by acting either as a transcriptional corepressor or coactivator (21)(22)(23)(24), our results show that HMMR is a target of MTA1 and that MTA1 enhances HMMR expression at the transcriptional level by directly interacting with the HMMR promoter as a part of the pol II⅐c-Jun complex. In support of this, we have also observed a strong meta-analysis correlation between MTA1 and HMMR in the tissue samples of both breast cancer and prostate cancer patients.…”
Section: Mta1 Expression Correlates With Levels Of Hmmr-amentioning
confidence: 81%
See 2 more Smart Citations
“…In this context, the studies presented here provide a mechanistic basis for the contribution of MTA1 in positively modulating HMMR expression, leading to cell invasion. As MTA1 regulates its target genes by acting either as a transcriptional corepressor or coactivator (21)(22)(23)(24), our results show that HMMR is a target of MTA1 and that MTA1 enhances HMMR expression at the transcriptional level by directly interacting with the HMMR promoter as a part of the pol II⅐c-Jun complex. In support of this, we have also observed a strong meta-analysis correlation between MTA1 and HMMR in the tissue samples of both breast cancer and prostate cancer patients.…”
Section: Mta1 Expression Correlates With Levels Of Hmmr-amentioning
confidence: 81%
“…Cell Culture and Antibodies-All of the cell lines used in this study were from the laboratory of R. K. and have been used previously (22,33,34). All of the cells were cultured in DMEM supplemented with 10% FBS and 1ϫ antibiotic solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified MTA1 as a transcriptional corepressor of the tumor suppressor gene PTEN, but contrary to earlier studies, for the first time, we found that MTA1 but not MTA2 associates with class II HDAC4s and identified the first target of the MTA1⅐HDAC4 containing the NuRD complex, the PTEN. In addition, MTA1 also forms a coactivator complex in association with RNA polymerase II, where it is recruited to the gene promoters such as BCAS3, Pax5, and Hyaluronan-mediated motility receptor (HMMR), and thereby promotes cancer invasion and migration (43)(44)(45). Recently, Salot and Gude (25) reported that MTA1 down-regulates the PTEN protein, not mRNA, and also proposed that MTA1 regulates the AKT pathway by inhibiting PTEN in cancer cells.…”
Section: Mta1 Expression Inversely Correlates With Pten Expresmentioning
confidence: 99%
“…MTA1, the founding member of the MTA family, is widely up-regulated in human cancers and involved in tumorigenesis, tumor invasion, and metastasis (3,4). MTA1 not only functions as a transcriptional repressor of its targets, such as estrogen receptor-␣ (5) and breast cancer type 1 susceptibility protein (BRCA1) (6), but also as a transcriptional activator via interacting with RNA polymerase II on the breast cancer-amplified sequence 3 (BCAS3) (7) and paired box gene 5 (Pax 5) (8) promoters. In addition to the well recognized role of MTA1 in tumorigenesis and tumor progression, emerging data suggest that MTA1 is a DNA-damage responsive protein as the intracellular levels of MTA1 are induced by ionizing radiation (IR), and plays an important role in DNA double strand break repair (9).…”
mentioning
confidence: 99%